Reanimating the tomb: Interpreting Palmyra’s banquet reliefs in context - Honeker, Kate (2023)
This thesis focuses on banquet scenes from the tombs of Roman Palmyra, Syria – relief sculpture depicting the deceased reclining on a kline, surrounded by his family in a commemorative tableau of elite values. In response to the scattering of thousands of pieces of Palmyrene funerary sculpture in museums across the world, this research explores meaning in the reliefs as impacted by, and inherently tied to, its original funerary context. Taking a holistic approach, iconographic study of tomb sculpture and wall painting is utilized alongside analysis of grave goods and tomb architecture to build a fuller picture of eschatological belief and mortuary activity connected to these spaces. Closing with a case study of the Hypogeum of Bolha and Borrefa, the banquet reliefs within are presented as the centrepiece of a dynamic, sensory space in which multiple elements interact and contribute to the overall construction of meaning.